2014
DOI: 10.7860/jcdr/2014/7094.4487
|View full text |Cite
|
Sign up to set email alerts
|

To Study the Levels of C - Reactive Protein and Total Leucocyte Count in Patients Operated of Open and Laparoscopic Cholecystectomy

Abstract: Background: The recovery from laparoscopic cholecystectomy (LC) is rapid and most of the patients are discharged on the 1 st post-operative day. There is an increased concentration of certain serum proteins, known as acute-phase reactive proteins (APRP) during the post-operative period depends on the degree of tissue damage and the inflammatory reaction. There is a direct positive correlation between the concentrations of APRP, especially C-reactive protein (CRP), and the severity of inflammation. This study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…On the other hand, measurement of insulin resistance using homeostatic model assessment-insulin resistance (HOMA-IR) has the same diagnostic value, and it is much simpler and cheaper. Positive correlation between HOMA-IR and CRP concentration and the severity of inflammatory response was reported in several studies (3, 4, 5, 6, 7). It was also demonstrated that postoperative insulin resistance is a temporary phenomenon for at least five days after uncomplicated cholecystectomy, particularly after an open approach (8).…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…On the other hand, measurement of insulin resistance using homeostatic model assessment-insulin resistance (HOMA-IR) has the same diagnostic value, and it is much simpler and cheaper. Positive correlation between HOMA-IR and CRP concentration and the severity of inflammatory response was reported in several studies (3, 4, 5, 6, 7). It was also demonstrated that postoperative insulin resistance is a temporary phenomenon for at least five days after uncomplicated cholecystectomy, particularly after an open approach (8).…”
Section: Introductionmentioning
confidence: 53%
“…Different results concerning postoperative levels of CRP were reported, favoring the laparoscopic approach over open surgery (30). CRP was superior to white cell count in predicting acute cholecystitis except in the case of pericholecystitis abscesses and biliary peritonitis due to gallbladder perforations when CRP and WBC performed equally well (14).…”
Section: Discussionmentioning
confidence: 99%
“…However, it has also been observed for cholecystectomies specifically that cytokine markers of inflammation and immunosuppression were significantly higher in LC over OC, although other studies have shown the opposite; that OC is associated with higher strain on the immune system. [16,17,23,24] Along with this, it has also been shown that the rate of surgical site infection in LC and OC is not significantly different, despite the increased incisional area in OC. [22] There are also still clear indications for OC to be performed, such as when the patient is unlikely to tolerate LC .…”
Section: Discussionmentioning
confidence: 71%
“…C-reactive protein (CRP) is an acute reactive protein (APRP) synthesized by the liver that can react with the C-polysaccharide in the Streptococcus pneumoniae capsule. 6 It is part of the non-specific immune mechanism, and its main biological function is to activate the classical pathway of complement by binding to ligands (phosphocholine of apoptotic and necrotic cells, or invading bacteria, fungi, parasites, etc. ), enhance leukocytophagocytosis, and stimulate the activation of lymphocytes or monocytes/macrophages as opsonins.…”
Section: Introductionmentioning
confidence: 99%